Performance Analysis and Response Time Optimization for Fiber Cut Handling Through a Proactive Monitoring Website to Improve Network Operational Efficiency - Samuel Restu Putra; Ahmad Fauzi; Dwi Wahyu Lestariningsih (Green Publisher Indonesia, 2025)
This study focuses on analyzing the performance and optimizing the response time in handling fiber cut disruptions using a proactive website monitoring system to improve network operational efficiency. Fiber optic networks are critical infrastructure in telecommunication services; however, frequent fiber cut incidents can disrupt connectivity and affect service quality. The research employs a quantitative approach with descriptive and comparative analysis to evaluate the effectiveness of proactive monitoring systems. Data from fiber cut incidents in Kalimantan, covering periods before (September–October) and after (November–December) proactive monitoring implementation, were analyzed. Results indicate a significant improvement in operational efficiency, achieving 72.77% efficiency, primarily due to a reduction in response time by 70.83%. However, the resolution time increased by 33.70%, attributed to factors such as team adaptation, complexity of incidents, and external conditions like weather. The Root Cause Analysis (RCA) identified primary disruption causes: multiple cuts, animal interference, government activity, and vandalism. The proactive monitoring system significantly enhanced the detection and response to incidents, demonstrating its potential as a critical tool in network management.